Physical pharmacy - Attwood, David; Florence, Alexander T. (London : Pharmaceutical Press, 2008)
A revision guide for students giving bullet points of basic information on physical pharmacy. This text is derived from the textbook Physicochemical Principles of Pharmacy and is designed to be used alongside it for those revision periods when time is short.
1. Solids; 2. Solubility and Solution Properties of Drugs; 3. Drug Stability; 4. Surfactants; 5. Emulsions, Suspensions and Other Dispersed Systems; 6. Polymers; 7. Drug Absorption; 8. Physicochemical Drug Interactions and Incompatibilities; 9. Peptides, Proteins and Other Biopharmaceuticals; 10. in Vitro Assessment of Dosage Forms; 11. Pharmaceutical Nanotechnology
Second edition 2012
Includes index.
PHR
Karim International
Keywords: Pharmacy -- Examinations -- Study guides; Pharmacy -- Study and teaching; Pharmacy -- Handbooks, manuals, etc; Pharmaceutical chemistry; Pharmacy